Feasibility, acceptability and impact of integrating malaria rapid diagnostic tests and pre-referral rectal artesunate into the integrated community case management programme. A pilot study in Mchinji district, Malawi. (December 2016) - Phiri, Themba; Kaunda-Khangamwa, Blessings; Bauleni, Andrew; Chimuna, Tiyese; Melody, David; Kalengamaliro, Humphreys; Sande, John; Nsona, Humphreys; Mathanga, Don
Abstract Background The World Health Organization recommends that persons of all ages suspected of malaria should receive a parasitological confirmation of malaria by use of malaria rapid diagnostic test (RDT) at community level, and that rectal artesunate should be used as a pre-referral treatment for severe malaria to rapidly reduce parasitaemia. This paper reports on findings from a pilot study that assessed the feasibility, acceptability and effects of integrating RDTs and pre-referral rectal artesunate into the integrated Community Case Management programme in Malawi. Methods This study used mixed methods to collect information for this survey. Pre- and post-intervention, cross-sectional, household surveys were carried out. A review of integrated community case management reports, including supervision checklists was conducted. Quantitative data were collected in tablets running on open data kit software, and then data were transferred to STATA version 12 for analysis. For key indicators, proportions were calculated at 95 % confidence intervals. Qualitative data were recorded onto digital recorders, translated into English and transcribed for analysis. Results Out of 86 observed RDT performances, a total of 83 (97 %) were performed correctly with a proper disposal of sharps and biohazard wastes. Only two (2 %) febrile children who had an RDT negative result were treated with artemether–lumefantrine, contrary to malaria treatment guidelines. Utilization of community health workers (CHWs) as a first source of care increased from (33.9 %) (95 % CI; 25.5–42.3) at baseline to (89.7 %) (95 % CI; 83.5–95.5) at end line in the intervention villages. There was a corresponding decrease in the proportion of caregivers that first sought care from informal sources from 12.9 % (95 % CI; 6.9–18.9) to 1.9 % (95 % CI; 0.9–4.4) in the intervention villages. Acceptability of the use of RDTs and pre-referral rectal artesunate at the community level was relatively high. Conclusion Integration of RDTs and pre-referral rectal at artesunate community level is both feasible and acceptable. The strategy has the potential to increase and improve utilization of child health services at community level. However, this depends on the CHWs' skills and their availability in remote areas.